Cat and Mouse in a Haunted House : Geronimo Stilton #3 - Stilton, Geronimo (New York Scholastic, 2004)
Geronimo Stilton discovers that the castle is haunted by cats.
3.
007-010.
Keywords: Mice -- Juvenile fiction; Cats -- Juvenile fiction; Adventure fiction; Ghost stories